Industrialization in sub-Saharan Africa seizing opportunities in global value chains - Abreha, Kaleb Girma; Kassa, Woubet; Lartey, Emmanuel; Mengistae, Taye; Owusu, Solomon; Zeufack, Albert G. (World Bank Group, 2021)
Industrialization drives the sustained growth in jobs and productivity that marks the developmental take-off of most developed economies. Yet, academics and policy makers have questioned the role of manufacturing in development for late industrializers, especially in view of rapid advancements in technologies and restructuring of international trade. Concurrently, industrialization and structural transformation are integral to the African Union's Agenda 2063 and the development strategies of several countries in Sub-Saharan Africa (SSA). Given this renewed interest in industrialization across the region, a central question is not whether SSA countries should pursue industrialization as a potential path to sustainable growth but how to promote the prospects of industrialization.
Tabellen, Literaturangaben
Keywords: INDUSTRIALIZATION; GLOBAL VALUE CHAIN; MARKET COMPETITION; SKILLS DEVELOPMENT; EMPLOYMENT; COMPARATIVE ADVANTAGE; KNOWLEDGE-INTENSIVE INDUSTRY